Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Pendekatan Saintifik di Kelas II SDN 12 Bukik Cangang Kota Bukittinggi - Masni, Nurbaiti; Zuryanty, Zuryanty (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study aims to describing the improvement of thematic learning process by using scientific approach in Grade 2 Elementary School of 12 Bukik Cangang at Bukittinggi cityi. This research used qualitative and quantitative approach. This research was classroom action research and had two cycles. The research subject was a teacher and 26 students of Grade II Elementary School of 12 Bukik Cangang Kota Bukittinggi.  The  study’s results shows the increasing in: Lesson plan of the first cycle is meeting 1 is 75%  (enaugh), meeting 2 is 81,25% (good),  and  the second  cycle meeting 1 is 97,22% (very  good). Teacher’s activities in first cycle meeting 1 is 65,63%  (enaugh), meeting 2 is 84,37% (good), the second cycle meeting 1 is 96,87% (very good). Student’s activities in first cycle meeting 1 is 56,25%  (less), meeting 2 is 81,25%  (good),  the  second  cycle meeting 1 is 93,75% (very good).the average of classin first cycle is 70,67, meeting 2 is 80,38, and the second cycle is 90,24. Therefore, the scientifict method can increase the integrated thematic learning at elementary school. Keywords : Integrated Thematic, Scientific Approach.